2003
DOI: 10.1046/j.1523-5378.2003.00121.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Infection, Mucosal Atrophy and Intestinal Metaplasia in Asian Populations: A Comparative Study in Age‐, Gender‐ and Endoscopic Diagnosis‐Matched Subjects

Abstract: Gastric ulcer was more common among Japanese subjects, while duodenal ulcer was more common among the other Asian populations examined. Japanese subjects with H. pylori infection showed more severe atrophic and metaplastic gastritis compared with that in other Asian subjects with H. pylori infection. These results may be related to the higher incidence of gastric cancer noted in Japanese subjects and the lower incidence of the cancer seen in Thai and Vietnamese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 17 publications
(27 reference statements)
4
48
1
Order By: Relevance
“…Also, GC develops in persons with H. pylori but not in uninfected persons. 23 Patients with gastritis (75%; 6/8), GU (70.8%; 17/24), DU (65%; 26/40), NUD (64.7%; 55/85), and GORD (64%; 29/45) also had high prevalence rates of the organism, which corroborates the findings of others 7,21 who reported either one or two of the above clinical conditions as the most common endoscopic findings in H. pylori infection. It has been suggested that up to 95% of DUs and 70% of GUs are attributable to infection by this pathogen, and most cases occur in middle-aged subjects.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Also, GC develops in persons with H. pylori but not in uninfected persons. 23 Patients with gastritis (75%; 6/8), GU (70.8%; 17/24), DU (65%; 26/40), NUD (64.7%; 55/85), and GORD (64%; 29/45) also had high prevalence rates of the organism, which corroborates the findings of others 7,21 who reported either one or two of the above clinical conditions as the most common endoscopic findings in H. pylori infection. It has been suggested that up to 95% of DUs and 70% of GUs are attributable to infection by this pathogen, and most cases occur in middle-aged subjects.…”
Section: Discussionsupporting
confidence: 85%
“…5,6 It plays a role in adenocarcinoma of the distal stomach, mucosaassociated lymphoid tissue lymphoma (MALT) and primary gastric non-Hodgkin's lymphoma, in many societies. 3,7 H. pylori's ability to adhere, invade and evade host defences and cause tissue damage is largely due to its production of colonisation and virulence factors. 8 The prevalence of H. pylori infection increases with advancing age and is higher in developing countries and among low socio-economic populations, probably owing to conditions that favour the infection, such as poor hygiene, crowded living conditions, and inadequate or no sanitation.…”
mentioning
confidence: 99%
“…H. pylori is the major cause of acute or chronic gastritis, peptic ulcerations (PU) disease, gastric adenocarcinoma and gastric mucosa-associated lymphoid tissue (MALT) lymphoma. In most of cases the infection remains asymptomatic during life, just 20% develops peptic ulcer or gastric carcinoma (Blaser, 1992a;Blaser, 1992b;Blaser and Parsonnet, 1994;Parsonnet et al, 1997;McColl and El-Omar, 2002;Sepulveda and Graham, 2002;Kapadia, 2003;Matsuhisa et al, 2003). The cag pathogenicity island (cag PAI) of H. pylori is an important virulence factor that involves several genes with different function in the H. pylori (Crabtree et al, 1995a;Crabtree et al, 1995b;Sharma et al, 1995;Tummuru et al, 1995;Censini et al, 1996;Figura and Valassina, 1999;Asahi et al, 2000;Stein et al, 2000;Megraud, 2001).…”
Section: Genotypes Predict Risk Of Peptic Ulcerations But Not Gastricmentioning
confidence: 99%
“…In Thailand, the incidence of HP infection is similar to other countries in Southeast Asia, with HP antibodies present in approximately 17.5% of children ages 5-9 years, but increasing to 75% in the 30-to 49-year-old group (Mahachai et al 2000). However, although there is a high preva-lence of HP infection in Thailand, the incidence of gastric atrophic changes, intestinal metaplasia, and gastric cancer are significantly lower than other countries (Atisook et al 2003, Matsuhisa et al 2003, Sriamporn et al 2002. The reasons for this paradox are not well understood but appear to be related to diet and life style (Bhamarapravati et al 2003).…”
Section: Introductionmentioning
confidence: 99%